PENGARUH INTERVAL TRAINING TERHADAP KECEPATAN LARI PADA SISWA EKSTRAKURIKULER MAN 1 MUARA FAJAR - Rendi Juanda; Slamet Slamet; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The problem with extracurricular students at MAN 1 Muara Fajar is the lack of speed when running 100 yards. This study aims to determine how much influence the interval training on running speed on students of athletic extracurricular MAN 1 Muara Fajar. This research is experimental research. The population in this study were extracurricular students, the sample in this study amounted to 8 people. The technique of collecting data through a 100 yard run test was conducted before and after conducting interval training. The data obtained were analyzed descriptively and inferentially. The hypothesis proposed in this study is that there is the effect of interval training on running speed on students of athletic extracurricular MAN 1 Muara Fajar. The results of the t-test results in a tcount of 1.69 and t table of 1.895 with an error rate of 0.05 (5%). Means tcount < ttable. This gives a conclusion that there is no significant effect of interval training on running speed in extracurricular students at MAN 1 Muara Fajar. It can be concluded that Ha is rejected.Keywords: Interval Training, Running Speed